Antibody and cytokine levels in humans fed on by the common bedbug, Cimex lectularius L. (March 2017) - Sheele, J. M.; Ridge, G. E.; Coppolino, K.; Bonfield, T.; Young, A. B.; Gaines, S. L.; McCormick, T. S.
Summary: Little is known about cimicosis, the resultant dermal reaction from feeding activity by the common bedbug, Cimex lectularius L. We fed C. lectularius on human study subjects four times over four weeks and measured serum cytokine and antibody levels, and subjects recorded any cimicosis. The average time for subjects to develop cimicosis decreased with each feeding from 8.4, to 2.1, 1.5 and 1.3 days, respectively. There were no significant changes in total IgG, IgG1, IgG2, IgG4 or IgE levels between the first and fourth bedbug feedings, but there was a significant decrease in total IgG3 levels ( P <.001). IgG4 was not required for cimicosis. Higher IgG2 and IgG4 levels at study visit 4 were associated with an increased duration of cimicosis ( P =.04) and lower pruritis ( P =.03), respectively. There were no significant changes in serum TNF‐α, IL‐1β, IL‐4, IL‐5, IL‐6, IL‐10, IFN‐γ and IL‐17A levels before and one hour after the C. lectularius feeding. Lower post‐ C. lectularius feeding IL‐6 levels were associated with increased pruritis ( P =.001) and the time to maximum pruritis ( P =.04), respectively. Higher post‐ C. lectularius feeding IL‐5 levels were associated with a longer duration of pruritis ( P =.05).